2017
DOI: 10.1051/0004-6361/201629845
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tunneling in H-abstraction reactions by OH radicals

Abstract: We present a combined experimental and theoretical study focussing on the quantum tunneling of atoms in the reaction between CH 4 and OH. The importance of this reaction pathway is derived by investigating isotope substituted analogs. Quantitative reaction rates needed for astrochemical models at low temperature are currently unavailable both in the solid state and in the gas phase. Here, we study tunneling effects upon hydrogen abstraction in CH 4 + OH by focusing on two reactions: CH 4 + OD − − → CH 3 + HDO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 81 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…The OH radicals are formed by H-atom addition to O 2 ) and the CH 3 radicals are formed by OHmediated H-abstraction of CH 4 (i.e., radicals are formed in situ). A series of control experiments performed by Lamberts et al (2017) showed that the produced OH radicals are solely respon- Table 1. Experiments performed in this study.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The OH radicals are formed by H-atom addition to O 2 ) and the CH 3 radicals are formed by OHmediated H-abstraction of CH 4 (i.e., radicals are formed in situ). A series of control experiments performed by Lamberts et al (2017) showed that the produced OH radicals are solely respon- Table 1. Experiments performed in this study.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…(♦) "(MWAS)" denotes species that were placed in the MWAS chamber. See also Section 3.2. sible for the H-abstraction of CH 4 (i.e., formation of CH 3 radicals directly through reaction with H-atoms is not efficient, as proved in Lamberts et al (2017)). We note that the formation of OH radicals from O 2 is not necessarily representative of the formation of OH radicals in low A V (low density) environments, where the O + H route dominates, as well as photodissociation of H 2 O.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare our instanton rate constants to one‐dimensional tunneling approximations and to rate constants obtained without tunneling. Even though these approaches have been used in our group's previous work, they have not yet been described in detail. In harmonic transition state theory, the potential energy surface around the reactant and the transition structure is approximated harmonically.…”
Section: Theorymentioning
confidence: 99%
“…However, in these regions, the water abundance is very low ( 10 −8 ) and the higher rate constants do not improve the efficiency of water formation above abundances of 10 −8...−9 (typical values reached by photodesorption in the outer disk). Lamberts et al (2017) and Beyer et al (2016), respectively. When using the fits to these rate constants in the T Tauri disk model, we did not find significant differences in the species abundances.…”
Section: Use Of Correct Reaction Rate Constantsmentioning
confidence: 99%